18F-Labeled indole-based analogs as highly selective radioligands for imaging sigma-2 receptors in the brain. Issue 14 (15th July 2017) - Wang, Liang; Ye, Jiajun; He, Yingfang; Deuther-Conrad, Winnie; Zhang, Jinming; Zhang, Xiaojun; Cui, Mengchao; Steinbach, Jörg; Huang, Yiyun; Brust, Peter; Jia, Hongmei
Graphical abstract: Abstract: We have designed and synthesized a series of indole-based σ2 receptor ligands containing 5, 6-dimethoxyisoindoline or 6, 7-dimethoxy-1, 2, 3, 4-tetrahydroisoquinoline as pharmacophore. In vitro competition binding assays showed that all ten ligands possessed low nanomolar affinity ( K i  = 1.79–5.23 nM) for σ2 receptors and high subtype selectivity ( K i (σ2 )/ K i (σ1 ) = 56–708). Moreover, they showed high selectivity for σ2 receptor over the vesicular acetylcholine transporter (>1000-fold). The corresponding radiotracers [ 18 F]16 and [ 18 F]21 were prepared by an efficient one-pot, two-step reaction sequence with a home-made automated synthesis module, with 10–15% radiochemical yield and radiochemical purity of >99%. Both radiotracers showed high brain uptake and σ2 receptor binding specificity in mice.